Implementing Qur’an-Hadith learning to foster students’ critical thinking skills - Fitri Aulia; Meiviani Nurul Aisyah Maulana; Salma Nadhifa Asy-Syahida; Taufiqurrohman Taufiqurrohman; Asep Nursobah (Universitas Pendidikan Indonesia, 2025)
This study examines the implementation of Qur’an-Hadith learning grounded in the values of tafakkur and tadabbur in QS Ali Imran: 190-191, which are closely related to the development of students’ critical thinking skills. This research was conducted to address the need for learning models in Islamic education that not only transfer religious knowledge but also foster higher-order thinking skills among vocational school students. The main purpose of this study is to explore how the study of the Qur’an and Hadith can be integrated into classroom activities to strengthen students’ analytical and reflective thinking, particularly in the context of health vocational education. Using a qualitative descriptive method, data were collected through observation, interviews, and document analysis involving PAI teachers and students at SMK Sentra Medika. The findings reveal that integrating Qur’anic values with reflective learning strategies, such as discussion-based activities, mindful learning, and contextual analysis, effectively encourages students to connect Qur’anic messages with real-life experiences and ethical issues in the health field. The study concludes that appropriately designed Qur’an-Hadith instruction can significantly contribute to the development of critical thinking skills and support the formation of spiritually and intellectually balanced learners. Abstrak Penelitian ini mengkaji implementasi pembelajaran Al-Qur'an-Hadis berbasis nilai-nilai tafakkur dan tadabbur dalam QS Ali Imran: 190-191, yang erat kaitannya dengan pengembangan keterampilan berpikir kritis siswa. Penelitian ini dilakukan untuk menjawab kebutuhan akan model pembelajaran dalam pendidikan Islam yang tidak hanya mentransfer ilmu agama tetapi juga menumbuhkan keterampilan berpikir tingkat tinggi di kalangan siswa sekolah kejuruan. Tujuan utama penelitian ini adalah untuk mengeksplorasi bagaimana pembelajaran Al-Qur'an-Hadis dapat diintegrasikan ke dalam kegiatan kelas untuk memperkuat kemampuan berpikir analitis dan reflektif siswa, terutama dalam konteks pendidikan kejuruan kesehatan. Dengan menggunakan metode deskriptif kualitatif, data dikumpulkan melalui observasi, wawancara, dan analisis dokumen yang melibatkan guru PAI dan siswa di SMK Sentra Medika. Temuan penelitian menunjukkan bahwa integrasi nilai-nilai Al-Qur'an dengan strategi pembelajaran reflektif seperti kegiatan diskusi, pembelajaran penuh kesadaran, dan analisis kontekstual secara efektif mendorong siswa untuk menghubungkan pesan-pesan Al-Qur'an dengan pengalaman hidup nyata dan isu-isu etika di bidang kesehatan. Studi ini menyimpulkan bahwa pembelajaran Al-Qur'an-Hadis yang dirancang dengan tepat dapat berkontribusi secara signifikan terhadap pengembangan keterampilan berpikir kritis dan mendukung pembentukan peserta didik yang seimbang secara spiritual dan intelektual. Kata Kunci: berpikir kritis; pembelajaran al-qur'an-hadis; pendidikan Islam vokasional; tafakkur dan tadabbur